A study on air quality and heavy metals content of urban food produced in a Mediterranean city (Barcelona). (10th September 2018) - Ercilla-Montserrat, Mireia; Muñoz, Pere; Montero, Juan Ignacio; Gabarrell, Xavier; Rieradevall, Joan
Abstract: Urban agriculture is growing in cities and is rising to the roofs of buildings. The potential food contamination is a key issue to be resolved to guarantee the health of consumers, and it affects both urban agriculture promoters and consumers. Crop contamination from the soil can be overcome by adopting a soilless cultivation system that, with good management practices, can also avoid contamination from the fertirrigation system and pest treatments. It has recently increased the number of soilless cultivation systems in cities due to the good features it offers. This study focuses on the potential contamination of heavy metals in hydroponic lettuce crops due to atmospheric pollution in high-traffic areas. The contents of heavy metal in the air and the lettuce leaves were measured at 4 sites: a periurban-integrated rooftop greenhouse, a periurban rooftop, an urban courtyard and an urban rooftop. High-volume sensors were used to assess air contamination. Lettuce leaves were analysed to evaluate the heavy metal concentrations. The results show that the heavy metal concentration in lettuce leaves is also below the EU-legislated limit in all studied cases. Specifically, the concentrations below the detectable analytic values were <0.02 mgNi/kg, <0.008 mgHg/kg, 0.005mgAs/kg and <0.005 mgCd/kg. The Pb concentration ranged from 0.0060 mg/kg to 0.0244 mg/kg. Although the chosen sampling locations were close to high-density roads and they are more vulnerable to a high concentration of metals, in the 4 sampling points heavy metal concentration in the air were less than 50% of the limits established in the legislation as the lower assessment threshold. This study concludes that the heavy metal content in the air of Barcelona is low and is not a source of contamination for urban crops including high traffic areas. Graphical abstract: Image